1997
DOI: 10.1093/rheumatology/36.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Salmon calcitonin nasal spray in the prevention of corticosteroid- induced osteoporosis

Abstract: The objectives were to determine the efficacy and safety of nasal salmon calcitonin 200 IU daily in the prevention of corticosteroid-induced osteoporosis. A minimized, double-blind, placebo-controlled trial was carried out in corticosteroid-treated patients with polymyalgia rheumatica. The setting was a tertiary care university-affiliated hospital and a total of 31 patients were enrolled. The primary outcome measure was the percentage change in bone mineral density of the lumbar spine in the two treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
7

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 12 publications
2
73
1
7
Order By: Relevance
“…A 2-year randomized clinical trial demonstrated the effi cacy of combined calcium and vitamin D supplementation in preventing bone loss in patients with rheumatoid arthritis treated with low doses of GCs [202] . These fi ndings were not reproduced in a 3-year follow-up study, where the same combination did not show any benefi t [203] . Randomized clinical trials and meta-analyses have shown that active metabolites of vitamin D ( ␣ -calcidiol and calcitriol) are more effective than vitamin D in maintaining bone density during medium-to-high dose GC treatment [204][205][206] .…”
Section: Therapeutic Optionsmentioning
confidence: 83%
“…A 2-year randomized clinical trial demonstrated the effi cacy of combined calcium and vitamin D supplementation in preventing bone loss in patients with rheumatoid arthritis treated with low doses of GCs [202] . These fi ndings were not reproduced in a 3-year follow-up study, where the same combination did not show any benefi t [203] . Randomized clinical trials and meta-analyses have shown that active metabolites of vitamin D ( ␣ -calcidiol and calcitriol) are more effective than vitamin D in maintaining bone density during medium-to-high dose GC treatment [204][205][206] .…”
Section: Therapeutic Optionsmentioning
confidence: 83%
“…It should be noted, however, that many of the patients in that study were vitamin D deficient. Adachi et al (73) have recently re-examined the effect of calciferol (50 000 U/week) plus calcium (1000 mg/day) in a randomised controlled trial. At the end of 3 years, they found no suggestion of any beneficial effect from the use of this intervention.…”
Section: Vitamin D and Its Metabolitesmentioning
confidence: 99%
“…Proposed treatments include bisphosphonates, hormone replacement therapy, vitamin D (cholecalciferol or calciferol) and calcium, calcitriol, calcidiol, alfacalcidol, calcitonin, fluoride, testosterone, and anabolic steroids (Adachi et al 1996, Ringe et al 1999, Eastell et al 2000, Boutsen et al 2001, Å strand & Aspenberg 2002, Crandall 2002, Sambrook 2007). In addition, several alternative therapeutic approaches have been considered in recent years.…”
Section: Introductionmentioning
confidence: 99%